High temperature carbonization of Turkish bituminous coals in Jenkner retort - Sutcu, H; Toroglu, I; Piskin, S (TAYLOR & FRANCIS INC, 2004)
Turkey started its history of bituminous coal with its discovery in 1829 in the Zonguldak Basin in Northwest Turkey. Today, the Zonguldak Basin contains almost 99% of the country's estimated 1.4 thousand million tons of bituminous coal reserves. Coal is mined by underground methods in five districts-Karadon, Uzulmez, Kozlu, Armutcuk and Amasra. The chemical or coking properties of the coal to be consumed in the production of coke has to be established in a laboratory on a small scale before being dispatched to the coke producing plant. Thus, the amount and properties of the coke and its by-products can be predicted as accurately as possible. The Jenkner High Temperature Carbonization System is one of the systems suggested to this end. This system can be operated at up to 1100degreesC and is designed so to make it possible to estimate the yield of the coke as well as the quantity of its by-products. The research was carried out on the samples extracted from eleven seams of bituminous coal most widely mined in the Zonguldak Basin. The coke obtained by means of carbonization was chemically analyzed and the composition of the coke gas was established by means of a gas chromatograph. In addition, a study was carried out on the effects of the chemical and petrographic properties of the coal seams on the composition of the coke, tar and the coke gas.
Keywords: bituminous coal; carbonization; char; gas; high temperature; Jenkner; tar; Zonguldak; Energy & Fuels; Engineering